The Influence of Communication Skill, Giving Incentives, Career Opportunities, Commitment and Organizational Culture on Employee Performance KSPPS Koperasi Pemuda Buana (KOPENA) Pekalongan - Sukardi Sukardi; Siti Aminah (AL-ARBAH: Journal of Islamic Finance and Banking, 2021)
AbstractPurpose - The purpose of this research to determine the Effect of Communication Skills, Incentives, Career Opportunities, Commitment and Organizational Culture on Employee Performance KSPPS Pemuda Buana Cooperative (KOPENA) Pekalongan.Method - The population in this study were 50 employees of the KSPPS Pemuda Buana Cooperative (KOPENA) Pekalongan. The sampling method that will be used in this study is the census sampling method of 50 respondents. Data analysis used multiple linear regression analysis.Result - The results of this study concluded that there is a positive and significant effect of communication skills. There is a positive and significant effect of providing incentives. There is a positive and significant influence of career opportunities. There is a positive and significant effect of commitment. There is a positive and significant influence of organizational culture.Implication - The implication is that communication skills, incentives, career opportunities, commitment and organizational culture will affect employee performance.Originality - This study analyzes Communication Skills, Incentives, Career Opportunities, Commitment and Organizational Culture will affect Employee Performance.